Development of wearable patch antenna for medical application - Za'aba, Ain S.; Ibrahim, Siti Noorjannah; Abdul Malek, Norun Farihah; Mohd Ramly, Athirah (IEEE, 2017)
This paper presents the development of a flexible antenna made of Polydimethylsiloxane (PDMS) and Copper (Cu) patch. The antenna comprises of Cu tape as the patch and ground plane, PDMS composite as the substrate and SMA connector as the coaxial feed with dimensions of 21.5mm patch radius, 60x60x3 mm3 substrate area and 60x60 mm2 ground plane area. In this study, we also create a PDMS+glass microsphere composite as substitute to the PDMS substrate. The PDMS+glass inclusion reduces PDMS’s relative permittivity and loss tangent to 1.9 and 0.014 respectively which could enhance antenna’s performance. To overcome adhesiveness issue between Cu patch and PDMS substrate, the antenna was encapsulated with another thin layer of PDMS/PDMS+glass substrate of 0.6mm thickness to ensure a constant distance from the ground plane. CST software was used to simulate antenna resonance frequency prior to the fabrication. Measurements using a Vector Network Analyzer (VNA) showed that the PDMS substrate antennas resonated at 1.92 GHz (without encapsulation) and 2.34 GHz (with encapsulation) while the PDMS+glass substrate antennas resonated at 2.46 GHz (without encapsulation) and 2.25 GHz (with encapsulation) respectively. Here, we also discussed the effect of substrate on return loss. Overall, results obtained from the measurements are in agreement with the simulation results.